Pendayagunaan Zakat Produktif Berbasis Al-Adl Dalam Meningkatkan Kesejahteraan Mustahiq di Wahdah Inspirasi Zakat Kota Makassar - Munawwarah Sahib; Jamaluddin Jamaluddin; Nur Ifna (Jurnal Iqtisaduna, 2023)
This research was conducted to find out to which the implementation of the utilization of productive zakat based on justice in increasing the welfare of mustahiq, this study used a qualitative descriptive analysis approach. Data collection used are observation, interviews, and documentation. The results of this study indicate that the empowerment of productive zakat is carried out in the form of providing business capital to micro and small business actors in three programs, namely business skills training, micro-enterprise development in the archipelago, and independent mother entrepreneurs. Utilization of productive zakat in the context of justice, Wahdah Inspirasi Zakat has applied the principles of justice in the process of utilizing zakat to mustahik, where the principle of justice in Islam is justice in a proportional form, namely by distributing zakat funds based on the level of need for mustahik on a priority scale, there are also the term justice in the form of equal rights and obligations in the sense of not discriminating between one mustahik and another mustahik, so that mustahik who have felt the benefits of zakat funds directed to productive activities can improve welfare and help meet the needs of their families in the future